2013
DOI: 10.1186/1475-2840-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus abrogates compensatory augmentation of myocardial neuregulin-1β/ErbB in response to myocardial infarction resulting in worsening heart failure

Abstract: BackgroundDiabetes mellitus (DM) patients surviving myocardial infarction (MI) exhibit a substantially higher incidence of subsequent heart failure (HF). Neuregulin (NRG)-1 and erythroblastic leukemia viral oncogene homolog (ErbB) receptors have been shown to play a critical role in maintenance of cardiac function. However, whether myocardial NRG-1/ErbB is altered during post-MI HF associated with DM remains unknown. The aim of this study was to determine the impact of type 1 DM on the myocardial NRG-1/ErbB sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The NRG-1/ErbB system is necessary for physiological adaptation of the heart to the changes of cardiac demand, and disruption of this system impairs recovery of cardiac contractile function [15]. Odiete et al reported diabetes can prevent compensatory up-regulation of myocardial NRG-1/ErbB after myocardial infarction coincident with an increased severity of heart failure [16]. Previous studies also reported NRG-1 can improve cardiac function in animal models of heart disease including ischemic, dilated, and viral cardiomyopathy [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…The NRG-1/ErbB system is necessary for physiological adaptation of the heart to the changes of cardiac demand, and disruption of this system impairs recovery of cardiac contractile function [15]. Odiete et al reported diabetes can prevent compensatory up-regulation of myocardial NRG-1/ErbB after myocardial infarction coincident with an increased severity of heart failure [16]. Previous studies also reported NRG-1 can improve cardiac function in animal models of heart disease including ischemic, dilated, and viral cardiomyopathy [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings and relevant literature, one could assume that CSC function would be further impaired, but this important point deserves further study. 30,31 Most importantly, current CSC culture standard operating procedures in clinical testing invariably subject cells to 25 mmol/L glucose culture conditions because this represents the industry standard for mammalian cell culture. The origin of this nonphysiological glucose content is based on the use of commercially sourced basal media formulations (Iscove's Modified Dulbecco's Medium), which early reports found enhanced hematopoietic cell proliferation.…”
Section: Molgat Et Al Effect Of Hyperglycemia On Cardiac Stem Cells S75mentioning
confidence: 99%
“…In animals, recombinant NRG-1 has beneficial effects on several forms of cardiomyopathy, including ischemic, toxic, viral, and diabetic cardiomyopathy (23,26). With specific relation to diabetes, endogenous NRG-1 signaling may be impaired in type 1 diabetic cardiomyopathy, while exogenous treatment with NRG-1 has reversed cardiac remodeling in diabetic rats (14,22,23,34). Currently, two forms of recombinant NRG-1 are being examined in clinical trials as potential therapies for heart failure with a reduced left ventricular (LV) ejection fraction (12,17).…”
mentioning
confidence: 99%